Inheritance of some reproductive traits by young bulls - J.H. Warren; J. Blum; R.R. Schalles; G. Kiracofe; K. Henry; V. Hultine (Kansas Agricultural Experiment Station Research Reports, 1976)
Severa1 reproductive traits of yearling Polled Hereford bulls were evaluated during and immediately after a 140-day feeding test. Results indicate that concentration of sperm and percentages of live sperm are heritable and genetically independent of each other. Heritability was low for sex drive or libido.
Keywords: Cattlemen& #x27; s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Reproductive traits; Heritability; Libido